MENINGKATKAN MOTIVASI BELAJAR PADA MATA PELAJARAN MATEMATIKA DENGAN PENGGUNAAN LAYANAN BIMBINGAN KELOMPOK - R.A Syifa Miftahul H; Syaifuddin Latif; Ranni Rahmayanthi (ALIBKIN (Jurnal Bimbingan Konseling), 2013)
The purpose of this study was to determine whether the motivation to learn on the subject of Mathematics can be enhanced with the use of group guidance services to students in class X SMA Negeri 1 Kotagajah. The problem in this study low student motivation to learn mathematics. The research problem is the motivation to learn on the subject of Mathematics can be enhanced with the use of group guidance services to students in class X SMA Negeri 1 Kotagajah.. The method used in this study pre-experimental method to design one-group pretest-posttest, and analyzed statistically using the non-parametric Wilcoxon test.The results obtained in the study show the motivation to learn mathematics has increased significantly after the administration of guidance services group. It is shown from the results obtained pretest and posttest zhitung = -2.521 and ztabel 0.05 = 4. Because zhitung ztabel then, Ho is rejected and Ha is accepted, it means there is a significant difference between the 5% level of motivation to learn mathematics scores before and after a given treatment is given to the treatment group guidance services to research subjects.Keywords: Group Counseling Services, Learning Mathematics Motivation